Evaluating the “Provision Related to the Absence of a Filed, Ongoing or Denied Lawsuit” Predicted for the Recognition of Decree Divorce Enacted by Administrative or Judicial Authorities of Foreign Countries within the Framework of State Register of Persons Item 27/A - Vildan Sezişli (Public and Private International Law Bulletin)
Recognizing the divorce verdicts rendered by the competent authorities of foreign countries is possible within the framework of the Regulation on Registration of the Decisions Given by the Judicial or Administrative Authorities of the Foreign Countries, the procedures and principles of which are related to the implementation of Article 27/A of the Civil Registry Services Act (CRSA). “The condition for the absence of no pending or dismissed lawsuit in Turkey regarding the decision” is required for the recognition of foreign divorce decisions pursuant to the Regulation on Registration of theDecisions Given by the Judicial or Administrative Authorities of Foreign Countries in the Civil Registers. Because the relevant regulation can be subject to different interpretations; this prevents the unity of practice. In our study, the recognition of a divorce decision given by the competent authorities of foreign countries is examined and discussed. Subsequently, the conditions required for the recognition of divorce decisions given by foreign judicial or administrative authorities in accordance with the Law on the application procedure were mentioned within the framework of the regulation in Article 27/A of the Civil Registry Cervices Act. After a study of the issues involved, the appropriateness of the “condition for the absence of lawsuit filed in Turkey regarding the decision that has still been ongoing or dismissed” in the Regulation on Registration of Decisions Given by Foreign Judicial or Administrative Authorities was evaluated.